A inovação disruptiva no segmento de pré-vestibular e os seus impactos nos modelos de negócios e capacidades dinâmicas - Falkembach, Marcos Morgental (2023)
Business history is full of examples of organizations that succumbed or were catapulted by innovations provided by technology. For a long time, the educational market seemed immune to the advances made by other sectors of the economy. Access to a quality pre-university entrance exam was, for a long time, a privilege for those coming from the higher social classes. The advent of online courses, starting in the 2010s, represents the emergence of a disruptive innovation that transformed the competitive dynamics of the sector, enabling the academic preparation of thousands of young students and imposing new challenges and opportunities for companies that operate in this market. Thus, the general objective of this work was to analyze how business models and dynamic capabilities are configured in a sector impacted by a disruptive innovation. To this end, a case study was adopted, whose data collection techniques consisted of a review of the international literature, observation and a structured interview with those responsible for the selected companies, with the purpose of identifying the strategies adopted for each of the nine components that make up the business model and the 12 variables that make up the developed dynamic capabilities. Among the results obtained, relevant differences and similarities can be observed in the business models of the courses that operate in face-to-face and online modalities, as well as in the dynamic capabilities produced by each of the companies that participated in the study. Among other things, it should be noted that digital platforms have allowed thousands of students to access quality pre-university entrance examination services, especially due to the low prices charged compared to their face-to-face peers. Due to their unique characteristics, improved over time, as advocated by the theory of disruptive innovation, it is clear that online courses attract more and more students from different profiles. On the other hand, as a differential for on-site courses, the importance of personal contact and the social dynamics represented by the interaction between students and other actors in this academic environment can be verified. Due to the volume of information arising from interactions between the customer base and the platform, online courses have the possibility of offering complementary services to students. It is also worth mentioning the importance that the profession of medicine has come to have for courses that operate in the pre-university entrance exam segment. It is noticed, among the companies surveyed, that there is not, among them, a point of convergence for the main resources component. Each of them pointed out different valences that justify the success of the course. With regard to the use of external partners for the development of innovation, it appears that there is a predilection for internalizing the main activities of the business, under the justification of giving autonomy and agility to the company. It was also observed that the COVID-19 pandemic helped to demystify the quality of the courses offered in the digital modality, which, in turn, created the opportunity for face-to-face courses to also start offering classes in the online format. Finally, it is worth noting that the companies have a decision-making process that encourages employees to participate in discussions involving work, have good levels of governance for the researched sector and demonstrate a culture of valuing knowledge.